An efficient plasticizer based on waste cooking oil: Structure and application. Issue 13 (28th October 2020) - Liu, Dekai; Shen, Yirui; Wai, Phyu Thin; Agus, Haryono; Zhang, Pingbo; Jiang, Pingping; Nie, Zhixin; Jiang, Guoqiang; Zhao, Huihang; Zhao, Minzhong
Abstract: Recently, phthalates have been continuously banned in numerous fields by many countries. Therefore, the development of sustainable and efficient plasticizers has become particularly urgent. The waste cooking oil was used as the main raw materials in this study to synthesize an efficient plasticizer (acetylated‐fatty acid methyl ester‐trimellitic acid ester, AC‐FAME‐TAE). The structure of AC‐FAME‐TAE was characterized by FT‐IR and 1 H NMR. The performance of the poly(vinyl chloride) (PVC) plasticized by AC‐FAME‐TAE was tested and compared with those of the PVC plasticized with di‐2‐ethylhexyl phthalate (DOP) and EFAME (epoxy fatty acid methyl ester), respectively. DSC results indicated that AC‐FAME‐TAE had excellent plasticizing efficiency for PVC. The mechanical properties of PVC plasticized by AC‐FAME‐TAE were as comparable as PVC plasticized by DOP from the results of tensile test. In addition, the PVC plasticized by AC‐FAME‐TAE had excellent thermal stability and solvent resistance by the results of leaching test and TGA. Abstract :